VD_FINDINFO AI 49/10 - 99/2012 vom 19. März 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, ACTIVITÉ LUCRATIVE À TEMPS PARTIEL | 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA